Dust Storm Aftermath - Farm Security Administration:::Creator::::::::::::
A barn, tree, and huddling chickens after a dust storm during the 1930's Dust Bowl. Cimarron County, on the western edge of Oklahoma, was severely affected by the Dust Bowl storms. It was the least populated and has the highest elevation (1500m) in the state. See also 1-213 and 1-214.